2014
DOI: 10.1103/physreva.89.042313
|View full text |Cite
|
Sign up to set email alerts
|

Family of[[6k,2k,2]]codes for practical and scalable adiabatic quantum computation

Abstract: In this work, we introduce a new family of [[6k, 2k, 2]] codes designed specifically to be compatible with adiabatic quantum computation. These codes support computationally universal sets of weighttwo logical operators and are particularly well-suited for implementing dynamical decoupling error suppression. For Hamiltonians embeddable on a planar graph of fixed degree, our encoding maintains a planar connectivity graph and increases the graph degree by only two. These codes are the first known to possess thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Interest in quantum annealing has piqued in recent years since com mercial processors comprising hundreds of programmable superconducting flux qubits have become available to the research community [10,11], and a lively debate has erupted concerning their quantumness [12][13][14][15][16][17][18][19] and the possibility of observing a quantum speedup [20][21][22], for which there exists theoretical evidence via specific examples [4,5,23], While error mitigation strategies for quantum annealing and, more generally, adiabatic quantum computing have been proposed [24][25][26][27][28][29][30][31][32][33] and implemented [34], much less is known compared to the relatively mature state of quantum error correction in the circuit model [1,35]. In particular, an accuracy threshold theorem [36][37][38] for fault-tolerant quantum annealing remains elusive, in spite of some degree of inherent robustness of adiabatic quantum computation to thermal excitations and control errors [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Interest in quantum annealing has piqued in recent years since com mercial processors comprising hundreds of programmable superconducting flux qubits have become available to the research community [10,11], and a lively debate has erupted concerning their quantumness [12][13][14][15][16][17][18][19] and the possibility of observing a quantum speedup [20][21][22], for which there exists theoretical evidence via specific examples [4,5,23], While error mitigation strategies for quantum annealing and, more generally, adiabatic quantum computing have been proposed [24][25][26][27][28][29][30][31][32][33] and implemented [34], much less is known compared to the relatively mature state of quantum error correction in the circuit model [1,35]. In particular, an accuracy threshold theorem [36][37][38] for fault-tolerant quantum annealing remains elusive, in spite of some degree of inherent robustness of adiabatic quantum computation to thermal excitations and control errors [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…V B), it is still clear that no useful AQC can take place: the ground state of H S (t) will, in general, be a coherent superposition of the complete set of eigenstates of the {A α } operators, and we have demonstrated that this superposition decays on multiple timescales, varying from the single-qubit dephasing time T to N times this timescale. Thus, to be able to perform useful AQC in the SCL under the independent decoherence model, one must invoke some form of error correction, suppression, or avoidance [42,[60][61][62][63][64][65][66][67][68].…”
Section: Independent Decoherencementioning
confidence: 99%
“…Therefore, any scalable quantum annealing architecture will require quantum error correction [25]. Unfortunately, theoretical progress in quantum error correction for adiabatic quantum computing and quantum annealing has not enjoyed the same success as that of other quantum computing paradigms, in spite of recent advances [26][27][28][29][30]. Physical constraints, such as locality of the interaction terms in the Hamiltonian [31,32], and a nogo theorem constraining what can be achieved with commuting two-local interactions [33], remain stubborn hurdles.…”
Section: Introductionmentioning
confidence: 99%